Clinical relevance of genetic polymorphisms in the human CYP2C subfamily - Goldstein, Joyce A (Blackwell Science Inc, 2001)
The human CYP2Cs are an important subfamily of P450 enzymes that metabolize approximately 20% of clinically used drugs. There are four members of the subfamily, CYP2C8, CYP2C9, CYP2C19, and CYP2C18. Of these CYP2C8, CYP2C9, and CYP2C19 are of clinical importance. The CYP2Cs also metabolize some endogenous compounds such as arachidonic acid. Each member of this subfamily has been found to be genetically polymorphic. The most well-known of these polymorphisms is in CYP2C19. Poor metabolizers (PMs) of CYP2C19 represent approximately 3–5% of Caucasians, a similar percentage of African-Americans and 12–100% of Asian groups. The polymorphism affects metabolism of the anticonvulsant agent mephenytoin, proton pump inhibitors such as omeprazole, the anxiolytic agent diazepam, certain antidepressants, and the antimalarial drug proguanil. Toxic effects can occur in PMs exposed to diazepam, and the efficacy of some proton pump inhibitors may be greater in PMs than EMs at low doses of these drugs. A number of mutant alleles exist that can be detected by genetic testing. CYP2C9 metabolizes a wide variety of drugs including the anticoagulant warfarin, antidiabetic agents such as tolbutamide, anticonvulsants such as phenytoin, and nonsteroidal anti-inflammatory drugs. The incidence of functional polymorphisms is much lower, estimated to be 1/250 in Caucasians and lower in Asians. However, the clinical consequences of these rarer polymorphisms can be severe. Severe and life-threatening bleeding episodes have been reported in CYP2C9 PMs exposed to warfarin. Phenytoin has been reported to cause severe toxicity in PMs. New polymorphisms have been discovered in CYP2C8, which metabolizes taxol (paclitaxel). Genetic testing is available for all of the known CYP2C variant alleles.